Korelasi Karakteristik dengan Penyebab Ketuban Pecah Dini pada Ibu Bersalin di RSUD Denisa Gresik - Renny Novi Puspitasari (Universitas Muhammadiyah Ponorogo, 2019)
Premature rupture of membrane (PROM) is rupture of the membrane before the birth time. It can happen in the end of pregnancy as well as the early pregnancy (premature pregnancy). The incident of PROM at Denisa Public Hospital Gresik reach 31%. PROM is high risk pregnancy, it was caused of predisposition factors such as incompeten cervix, uterus overdistension, the abnormal position, CPD, and infection. The purpose of this research is to identify the correlation of characteristics with causes of PROM at Denisa Public Hospital Gresik. This research is using analytics method by using simple random sampling. The sampel has been taken of 59 respondents from 143 of population, it begining of march 2017 until march 2018. The variable of this research is characteristics and the causes of PROM. The measurement tools were used check list and data was analyzed using chi square test with the alpha of 5%. The result showed that the factors that cause premature rupture of membranes in this study include: incompetent cervix, uterine overdistention, location abnormalities, CPD and infection. Maternal age correlates with incompetent cervical events, CPD and infections, while maternal work is associated with location abnormalities. So that risk screening at the beginning of pregnancy and routine ANC examination is very necessary.